Complexometric Determination of Chromium(III) from Binary and Ternary Mixtures Using 3-Hydroxy-3-Phenyl-1-m-Nitrophenyltriazenes as Metallochromic Indicator - K. Paliwal, Krishna; K. Gouri, Deepika; Kumar, sanjay; Moulakha, Neelam; Goswami, A.K.; Purohit, D.N. (Asian Journal of Chemistry, 2010)
A method for the use of 3-hydroxy-3-phenyl-1-m-nitrophenyl-triazene as metallochromic indicator for the complexometric determination of chromium(III) and for the complexometric determination of Cr(III) by kinetic masking in presence of other metal ions viz. Fe(IlI), Cu(II) and Ni(II) in binary mixtures containing ion pairs Cr(III), Fe(III), Cr(III), Cu(II) and Cr(III)-Ni(II) has been described. The study has been further extended to determine Cr(III) in ternary mixtures cotaining any of the three ions, viz., Cr(III)-Fe(III)-Cu(II), Cr(III)-Fe(III)-Ni(II) and Cr(III)-Cu(III)-Ni(II). The amount of metal ions found was in good agreement with the amount of metal ions actually present; so the determinations are quite accurate. For the sake of comparison parallel titrations were carried out using xylenol orange as indicator. This establishes use of hydroxytriazene as metallochromic indicator for Cr(III) determination.